Financial management practices: Associations with financial well-being and risky investment among families in Malaysia / Husniyah Abd. Rahim @ Abdul Wahab - Husniyah, Abd. Rahim (2010)
Financial management practices predicting good financial well-being and participation in risky assets among families were identified in this study. It also seeks to find out other factors predicting financial well-being and participation in risky assets. Associations of time horizon with risk preference, and risk preference with financial management practices, differences in financial management practices among the main ethnicities in Malaysia and among families residing in urban and rural areas were also determined. The moderating roles of self-worth between financial management practices and financial well-being of families, and between financial management practices and risky investment by families were explored. Quota sampling was employed to gather data from 800 samples who were the family financial managers using questionnaire forms through their work-place. Pearson correlation test revealed that time horizon of financial managers, measured by future time orientation was significantly associated with their risk preferences. Furthermore, the results from correlation tests showed that families having financially risk averse family financial managers were more likely to engage in financial planning, cash-flow activities, good credit practice, savings, and risk management. However, families having financially risk tolerance family financial managers were more likely to participate in diversified investment. Test of significant difference result indicated that Chinese families were more involved in diversified investment as compared to the Malay or Indian families. Moreover, the t-test resulted in the Chinese families to be more likely purchasing various types of insurance policies as compared to the Indian families. As for the differences in residential areas, the urban residents were more involved in record-keeping, diversified investment, and tend to purchase various types of insurance as compared to the rural residents. Binary logistic regression analysis revealed factors predicting financial well-being and participation in risky assets. Income, working experience, budgeting, and investment were found to be predictors for good financial well-being. A family that was financially stable tends to earn high household income with longer working experience, participated in diversified investment, and did budgeting for the family expenses. The tendency to participate in risky investment was positively influenced by their risk tolerant, savings, record-keeping, and risk practices. However good credit practices was inversely predicting participation in risky assets. These findings provided evidence that specific financial management practices did have impact on financial well-being and participation in risky assets. The socioeconomic characteristics identified for financially stable family and the financial management practices carried out by them would assist interested parties to help families who are at most risk of financial instability. Self-worth of family financial manager was found to moderate the relationships of financial planning and cash-flow with financial well-being of families. It also acts as a moderator for the relationship between risk practices and risky assets investing. The support found for the moderating roles of self-worth contributed to the family financial management and investment decision fields. The findings also offer important implications to financial educators and families in iv enhancing financial stability and reducing financial risks in investment through financial management strategies.